THE CYTOTOXICITY ACTIVITY OF ETHANOLIC EXTRACT OF ACANTHUS ILICIFOLIUS L LEAVES USING BRINE SHRIMP LETHALITY TEST (BSLT) METHOD - Sari, Dyah Ratna Ayu Puspita; Ugrasena, Putu Yudha; Ekayani, Ni Wayan Ria (Universal Journal of Pharmaceutical Research, 2022)
Aim and objective: Acanthus ilicifolius also known as jeruju is a plant that has a lot of bioactivity that can be used as a potential medicinal plant development. This study aimed to determine the cytotoxicity activity of ethanol extract of A. ilicifolius leaves. Methods: This study used Brine Shrimp Lethality Test (BSLT) method using Artemia salina larvae with test solution series concentration of 10, 50, 100, 500, 1000 ppm and control without extract. A. salina was added to each test tube. After 24 hours, the larvae mortality was observed. LC50 assessment was analyzedwith probit analysisby Microsoft excel. Result: The largest mortality percentage was shown at a concentration of 1000 ppm ethanol extract of A. ilicifolius leaves with an average mortality value of 80%, while the concentrations of 10 ppm, 50 ppm, 100 ppm, and 500 ppm had an average mortality value of 20%, 40%, 57% and 63%.The ethanol extract of A. ilicifolius leaves categorized as toxic with a LC50 value of 103,6 ppm. Conclusion: It was concluded that ethanol extract of A. ilicifolius leaves has cytotoxicity activity potential. Peer Review History: Received: 2 December 2021; Revised: 6 January 2022; Accepted: 9 February, Available online: 15 March 2022 Academic Editor: Dr. Gehan Fawzy Abdel Raoof Kandeel , Pharmacognosy Department, National Research Centre, Dokki, 12622, Giza, Egypt, gehankandeel9@yahoo.com Reviewers: Ahmad Najib, Universitas Muslim Indonesia, Makassar, Indonesia, ahmad.najib@umi.ac.id Dr. A.A. Mgbahurike, University of Port Harcourt, Nigeria, amaka_mgbahurike@yahoo.com